Improvements in Pain, Well-being, Arterial Pressure, and Lower Limb Volume Following Andullation Therapy in Healthy and Unhealthy Humans. Issue 2 (9th May 2019) - Parras-Moltó, Alba; Ribas-Serna, Juan
Our aim was to test the effects of Andullation therapy on pain threshold, pain perception, feeling of well-being, arterial pressure, and leg volume in healthy and unhealthy patients. We used a multidirectional vibration (frequency range: 5–40 Hz; peak-to-peak amplitude: 2–8 mm; acceleration: 0.4–2 m/s 2 ) in an undulatory way through the surface of the body when the patient was in contact with a mattress ("andullation"). The vibes traveled from the heel to the head in a random fashion while the participants (N = 50) were lying on the mattress. We measured the pain threshold using an algometer; pain perception and well-being through a visual analog scale (VAS); arterial pressure with an electronic sphygmomanometer; and leg volume with Kuhnke's technique. Measurements were made just before the first andullation session and after the fifth andullation session. Every participant received andullation sessions of 30 min a day for 5 consecutive days. The patients' pain threshold significantly ( P < .001) increased by 34.48% and 25.79% in the lumbar and trapezius zones, respectively, after 5 sessions of therapy. The subjective perception of pain decreased by 52.3% and the feeling of well-being increased by 45.1%. The systolic and diastolic pressures significantly ( P < .001) decreased by 6.44 and 4.68 mm Hg on average, respectively. Leg volume significantly decreased ( P < .01) by 64.39 mL after the fifth andullation session. Despite not including a control group in our study, the andullation intervention showed an improvement in pain, well-being, arterial pressure, and lower limb volume in the studied population.